2012
DOI: 10.1111/j.1524-4725.2012.02482.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Dermatofibrosarcoma Protuberans in Alberta, Canada, from 1988 to 2007

Abstract: The age-standardized incidence of DFSP observed is nearly twice as high as previously reported and has remained stable. The incidence is increasing in women and decreasing in men. DFSP primarily affects young to middle-aged adults and most commonly presents on the trunk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
22
0
4
Order By: Relevance
“…The few published population-based studies have shown that DFSP is a relatively rare tumour with age-adjusted rates of less than 1 per 100,000 inhabitants per year) [5,6]. Recent increase in incidence may be explained by a wider knowledge of the tumour among pathologists [6].…”
Section: Definition; Pathophysiology; Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The few published population-based studies have shown that DFSP is a relatively rare tumour with age-adjusted rates of less than 1 per 100,000 inhabitants per year) [5,6]. Recent increase in incidence may be explained by a wider knowledge of the tumour among pathologists [6].…”
Section: Definition; Pathophysiology; Epidemiologymentioning
confidence: 99%
“…Recent increase in incidence may be explained by a wider knowledge of the tumour among pathologists [6]. Because of the decline in developed countries of the incidence of HIV-associated Kaposi's sarcoma, DFSP is nowadays in some countries the most common form of skin sarcoma.…”
Section: Definition; Pathophysiology; Epidemiologymentioning
confidence: 99%
“…Dermatofibrosarcoma protuberans (DFSP) is a superficial soft tissue sarcoma with an incidence of 4 in 1,000,000. 1,2 DFSP often presents as a slow-growing, nodular, dermal lesion, with unexpectedly wide, impalpable, subcutaneous tumor extensions. It is known for its locally aggressive growth pattern and high local recurrence rates after incomplete resection (range, 2%-21%), but it has a low potential to metastasize (range, 1%-4%).…”
Section: Introductionmentioning
confidence: 99%
“…3 DFSP is most frequently identified in men and women between ages 20 and 40 years. 1,2 The mainstay of treatment is wide local excision, preferably with a surgical margin of at least 3 cm. [4][5][6][7] In 3% to 20% of patients with DFSP, fibrosarcomatous (FS) change is observed on histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of published pediatric cases ranges from 4.5% to 20% (3,(9)(10)(11)(12). Although there is unanimous agreement that DFSP is uncommon in children, it has been the subject of little epidemiologic research in this age group (13)(14)(15)(16)(17)(18)(19). Fewer than 200 cases have been reported in the literature (8,20,21).…”
mentioning
confidence: 99%